"Muddily Human": antimodernism in the novels of Robert Kroetsch - Clarke, Bronagh (2007)
For many years the novels of Robert Kroetsch have been canonized as paradigmatic Canadian postmodern and postcolonial texts. This thesis argues that Kroetsch’s texts are antimodernist works which reveal his reaction against modernity. This thesis explores each of Kroetsch’s novels in chronological order, from the unpublished text When Sick for Home to his most recent novel The Man from the Creeks, arguing that Kroetsch’s novels should be viewed as texts that demonstrate his antipathy towards modernity, which is manifested in Kroetsch’s nostalgic idealization of the imagined organic wholeness of a world existing prior to modernization. Throughout this thesis I discuss the parallels between the writings of Robert Kroetsch and Marshall McLuhan, emphasizing the antimodernism that underpins their works. I argue that their antimodernism signals their participation in a tradition of the critique of modernity. By foregrounding the idea of the modernist critique of modernity, which comprises an important element of artistic modernism, I question the privileging of the qualifier “post-” in constructions of the Canadian postmodern canon. In foregrounding the antimodernism evident throughout Robert Kroetsch’s fiction, I interrogate the construction of Canadian postmodernism in his own works and those of other Canadian critics including Linda Hutcheon. Through my analysis of the recurring motifs of the wilderness and the rural environment in Kroetsch’s work, I locate his fiction within Western antimodernist tradition, interrogating cultural nationalist constructions of Canadian postmodernism as an autochthonous phenomenon.